ChemInform Abstract: Asymmetric Synthesis of Pyrrolidine and Piperidine Derivatives via Regio‐ and Stereo‐Selective Ring‐Opening Reactions of Chiral Aziridine. Issue 18 (11th April 2013) - Higashiyama, Kimio; Matsumura, Masataka; Kurita, Emiko; Yamauchi, Takayasu
Abstract The reaction of aziridine (IV) with acetic acid leads to β‐amino alcohol (VI), which is converted into (S)‐prolinol.